PENINGKATAN KESADARAN POLA HIDUP MASYARAKAT BERSIH DALAM KONTEKS MODERASI BERAGAMA DI DESA MAEN - Alon Mandimpu Nainggolan; Megaputri Gagola; Widyarti Saliada; Marchel Gani; Farno Billy Arthur Gerung (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
Environmental cleanliness is not only focused on activities to minimize waste. However, it also talks about how people have the awareness to implement a healthy lifestyle. The community should try to see the condition or condition of the environment/region of the Maen village community themselves. The Maen village community is the driving force in implementing and achieving this lifestyle, with creative ideas and innovations needed to encourage each other in the success of environmental hygiene. With this Research Community Service program, implementing environmental hygiene encourages the formation of solidarity in religious moderation, in the sense of realizing cooperation for all Maen village communities regardless of religious background. Therefore, it is essential to implement the ABCD (Asset Based Community-driven Development) approach to develop an asset or what strength exists in the community. Strive to change the community's mindset so that they have awareness in responding to existing assets or strengths. Thus, KKN Research and the village government, and even religious leaders are trying to keep the environment free from waste problems.